Rethinking the public loggia to improve urban resilience to climate change - Carlos Mourão Pereira; Teresa Valsassina Heitor; Ann Heylighen (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Microclimates within loggia spaces near public walkways and building entrances are potentially strategic for resilience to extreme weather conditions. However, the public loggia may also be a space of conflict of appropriation and vulnerability, resulting in obsolete voids problematic for buildings and cities. This raises questions about its morphology and essential requirements to improve its functional performance. Therefore, a transdisciplinary study based on qualitative research was developed combining spatial experiences of experts and users. The results suggest that a public loggia needs to consider local climate, social behaviour, usability, urban cleaning, visibility and connections, as far as possible, with the main urban walkways. The findings also suggest that the public loggia only contributes toward urban resilience if its architectural details approach affordances and diversity within its users.